(untitled) (Research, Society and Development, 2021)
Introduction: Self-medication is a dangerous practice due to its harmful effects on health. Studies on self-medication among nursing students can foster health education and interventionist practices in undergraduate courses. Objective: Conduct a pedagogical workshop, as a form of intervention, aimed at health education on the practice of self-medication among nursing students in a higher education institution. Methods: Study of qualitative approach of the research-action type using as basis the theory of problematization the arch of Charles Maguerez. The study sample consisted of 21 nursing students from a higher education institution. Results: It was observed that most students use over-the-counter medications, among the symptoms that lead them to take medications are headaches, muscle pain, flu, inflammation, cough, heartburn, fever and menstrual cramps, the most used drug classes are analgesics, anti-inflammatory and antipyretics. Self-confidence in self-medicating is strongly related to the fact that they have already taken the course of drug therapy, despite being aware of the risks, a fact that corroborates the practice of recommendations for family and friends. Final Considerations: The study provided relevant information and knowledge regarding the phenomenon of self-medication among nursing students, after the workshop, the students showed interest in suspending the practice of self-medication, in addition to passing on the knowledge acquired to family and friends.